2014
DOI: 10.4103/2230-8598.133118
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of nutritional status of children aged 0-14 years in a slum area of Kolkata

Abstract: Introduction: Under-nutrition contributes to more than one-third of all deaths in children. It does this by diminishing children's immunity and making illness more dangerous. The primary aim of the study is to assess the nutritional status of children aged from 0 to 14 years in a slum area of Kolkata and secondary aim is to determine the prevalence of under-nutrition and its association with various risk factors among the study population. Materials and Methods: Community-based cross-sectional analytical study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 8 publications
2
2
0
Order By: Relevance
“…Taking different indicators of undernutrition into account, wasting (23.3%), stunting (57.4%), and underweight (45.4%), found in the children under study, is unacceptably high. Most studies worldwide have also reported high rates of undernutrition among slum children [8, 13–16]. The results of the present study are consistent with these findings.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Taking different indicators of undernutrition into account, wasting (23.3%), stunting (57.4%), and underweight (45.4%), found in the children under study, is unacceptably high. Most studies worldwide have also reported high rates of undernutrition among slum children [8, 13–16]. The results of the present study are consistent with these findings.…”
Section: Discussionsupporting
confidence: 93%
“…The sample size of 190 was calculated assuming the prevalence of undernutrition as 45% [8], precision of 10% at 95% confidence interval, with a design effect of 2. Multistage cluster random sampling technique was adopted to select the study population.…”
Section: Methodsmentioning
confidence: 99%
“…age (Mandal et al, 2014). The high percentage of stunted children in the surveyed population is particularly concerning in light of our results that support an association between stunting and motor proficiency.…”
Section: Discussionsupporting
confidence: 56%
“…Kolkata is a major metropolitan city in India whose inhabitants belong to different socio-economic classes. A wide range of chronic undernutrition among 5-12year-old Kolkata school children has been reported (Das, Basu, Dhar, Mallik, & Pal, 2012;Ghosh, Chowdhury, Chandra, & Ghosh, 2015;Mandal, Prabhakar, Pal, Parthasarathi, & Biswas, 2014). There is very limited literature on the relationship between the grades of chronic undernutrition and SES on motor performance, especially in children from developing countries like India.…”
Section: Introductionmentioning
confidence: 99%